Jane Fonda at Watkins' Home re Campaign for Economic Democracy Fundraiser - Watkins, Howard::::::::: (1982)
Doreen Gomez on crutches, Joe Floyd Asher and Jane Fonda, Katie Rea in Watkins family living room